Diskusi Kepemiluan Tahun 2024 Bersama Masyarakat di Desa Suka Rahmat Teluk Pandan - Safitri W., Dilla; Muhabibudin, Nur; Hayati, Imrona; Rosalina, Desi; Rusmiati, Rusmiati; Havid, Winda; Ayni, Nurul (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
Elections are an important element of democracy. In fact, in many democratic theories, elections are an indicator for measuring the quality of democracy. If a country has carried out an election process well, transparently, fairly, regularly and continuously, then that country can be said to be a country with a good level of democracy, but on the contrary if a country does not carry out elections or is unable to carry out elections well which is characterized by the occurrence of various cheating, discrimination and manipulation then the country is also considered an anti-democratic country. In this case, the public is the main target in understanding elections peacefully, critically and transparently from the start in order to avoid fatal mistakes regarding the elections that will be held in 2024. This Election Discussion will be provided with various things from Bawaslu and the surrounding KPU, so that the public can discuss what people should do so that they are not swayed by cases of money politics which have many negative impacts on a country and will turn a country's government into corruption so that the nation's paradigm becomes damaged and away from good democracy. The PKM that we carry out is based on the emergence of many problems among the community that can attract attention as the election approaches. The method we use in this PKM is descriptive qualitative, where the results of this PKM will then be described. From the PKM that we have carried out, it can be found that there is an increase in understanding from the public, especially young people rather than older people, about how to carry out elections peacefully, critically and transparently in order to make this country a country that has a better democracy in the future through understanding from the KPU and Bawaslu.